2004
DOI: 10.4049/jimmunol.172.5.3268
|View full text |Cite
|
Sign up to set email alerts
|

Lymphoma B Cells Evade Apoptosis through the TNF Family Members BAFF/BLyS and APRIL

Abstract: The mechanisms underlying the autonomous accumulation of malignant B cells remain elusive. We show in this study that non-Hodgkin’s lymphoma (NHL) B cells express B cell-activating factor of the TNF family (BAFF) and a proliferation-inducing ligand (APRIL), two powerful B cell-activating molecules usually expressed by myeloid cells. In addition, NHL B cells express BAFF receptor, which binds BAFF, as well as transmembrane activator and calcium modulator and cyclophilin ligand interactor (TACI) and B cell matur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
176
3
3

Year Published

2006
2006
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 261 publications
(194 citation statements)
references
References 75 publications
12
176
3
3
Order By: Relevance
“…The anti-apoptotic protein Bcl-2 is induced by APRIL in B-cell lymphoma. 2,3 Since high Bcl-2 expression is associated with poor chemotherapy response, 11,12 we investigated the relationship between APRIL and Bcl-2 in AML. Western blotting analysis showed that exogenous expression of APRIL up-regulated Bcl-2 in CD34 + cells, whereas APRIL neutralization resulted in Bcl-2 downregulation in primary AML cells ( Figure 3A, B), suggesting that APRIL protects AML from chemothereutic drugs through the upregulation of Bcl-2.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The anti-apoptotic protein Bcl-2 is induced by APRIL in B-cell lymphoma. 2,3 Since high Bcl-2 expression is associated with poor chemotherapy response, 11,12 we investigated the relationship between APRIL and Bcl-2 in AML. Western blotting analysis showed that exogenous expression of APRIL up-regulated Bcl-2 in CD34 + cells, whereas APRIL neutralization resulted in Bcl-2 downregulation in primary AML cells ( Figure 3A, B), suggesting that APRIL protects AML from chemothereutic drugs through the upregulation of Bcl-2.…”
Section: Resultsmentioning
confidence: 99%
“…APRIL (a proliferation-inducing ligand), is a member of the TNF superfamily expressed in B-cell progenitors, monocytes, dendritic cells, and megakaryoblasts, which may contribute to the development of B-cell malignancies, including non-Hodgkin's lymphoma (NHL), B-CLL and multiple myeloma (MM), through the enhancement of cell survival and proliferation. [1][2][3][4][5][6] APRIL is a homotrimeric type 2 transmembrane protein that also exists in soluble form deriving from the intracellular cleavage of the full-length protein. It can bind with high affinity to two members of the TNFreceptor superfamily, the B-cell maturation antigen (BCMA) and the transmembrane activator and calcium modulator and cyclophilin ligand-interactor (TACI).…”
Section: Introductionmentioning
confidence: 99%
“…96,97 Indeed, constitutive activation of the NF-kB pathway results in B-cell hyperplasia and obviated the BAFF-R-dependence of B-cell development. It also blocked the nuclear translocation of protein kinase C-d, which had been shown to induce the death of B-cells by phosphorylating histone H2B upon growth factor withdrawal.…”
Section: Tnf Family Members In B-cell Developmentmentioning
confidence: 99%
“…In contrast to most TNF family members, APRIL is processed in the Golgi apparatus into the active soluble form by a furin convertase (Lopez-Fraga et al, 2001). APRIL is expressed by a subset of immune cells that also produce B-cell activating factor (BAFF): monocytes, macrophages, (Hahne et al, 1998;Nardelli et al, 2001;He et al, 2004;Chu et al, 2007) as well as in some non-immune cells such as epithelial cells and osteoclasts. Moreover, PRIL is abundantly expressed in a variety of tumor cells and tissues, such as lung carcinomas, melanoma (Roth et al, 2001;Stein et al, 2002), lymphoid malignancies (Nardelli et al, 2001;Deshayes et al, 2004;Kern et al, 2004;Moreaux et al, 2004;Chiu et al, 2007;Pelekanou et al, 2008;Yaccoby et al, 2008) and in particular gastrointestinal tumors including rectum, duodenum, colon, stomach and esophagus (Hahne et al, 1998;Kelly et al, 2000).…”
Section: Introductionmentioning
confidence: 99%